Information and Communication Technologies Applied to Organizational Competitiveness in a Funeral Services Organization in Lima - Santur Aldaz, Lucia Nayelli; Lopez Vera, Nicole Alessandra; Gasparrini Cañas, Victor Gerardo; Saldaña Narro, Julio Brayan; Marcelo Quispe, Luis Alberto; Olórtegui Alcalde, Luis Miguel (LACCEI, 2025)
The main purpose of the study was to analyze the relationship between information and communication technologies and organizational competitiveness in a funeral services organization. The research has a quantitative, applied approach and correlational scope, based on a non-experimental design. The sample consisted of 143 employees of the company under study. To collect the data, two questionnaires were used, the first one with 22 items intended to measure the ICT variable and the second with 18 items intended to measure the organizational competitiveness variable. Both instruments reported very high reliability, verified through the Cronbach coefficients of 0.928 and 0.918, respectively. The results showed a statistically significant correlation (ρ = 0.672, p < 0.001) between the two study variables, indicating a positive relationship of moderate magnitude. In conclusion, it is inferred that the implementation and use of information and communication technologies will allow organizations to reach important levels of competitiveness.